Readability of the Transactional Texts in Bahasa Inggris Textbook for Grade X - Sujatna, Eva Tuckyta Sari (International Journal of Systemic Functional Linguistics, 2019)
This paper aims are lexical density and grammatical intricacy of the transactional texts in Bahasa Inggris as one of the English textbooks for senior high students (grade X) in Indonesia. The method applied is qualitative research method. The study supported by three methods in determining readability as proposed by Halliday (1985, 1994, 2004), Ure (1971), and a text analyzer adapted from www.usingenglish.com as the website that provided the tool. The data are taken from the textbooks as transactional texts. The texts obtained are six transactional texts. The results of the study have shown several valuable insights. Firstly, the transactional text that has the highest number of words (530 words) containing highest number of sentences could be categorized into the spoken text (lexical density= 26.44) and the level is under Easy Reading Range (Fog Index = 4.23) as described in T6. Secondly, the total unique words in transactional text has relation with hard words, lexical density and Fog Index as described in the T2. Thirdly, the lowest number of words could relate to the unique words and total number of sentences (as seen in T4). To choose the transactional text given as the material in Bahasa Inggris, it is suggested that the writer of the textbooks should be more thoughtful in deciding the transactional texts level chosen since the data shows that the level of the text is various (Fog Index 4.23 as the lowest – 10.25 as the highest) and the average transactional text level is 6.7.